2017
DOI: 10.1159/000484257
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein Cleaves C3 and Activates Complement

Abstract: The human plasma contact system is an immune surveillance system activated by the negatively charged surfaces of bacteria and fungi and includes the kallikrein-kinin, the coagulation, and the fibrinolytic systems. Previous work shows that the contact system also activates complement, and that plasma enzymes like kallikrein, plasmin, thrombin, and FXII are involved in the activation process. Here, we show for the first time that kallikrein cleaves the central complement component C3 directly to yield active com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 41 publications
(51 reference statements)
4
71
2
1
Order By: Relevance
“…The regulation of extracellular proteolysis is critical to blood hemostasis and innate immunity and proteases plasma prekallikrein (PK), and coagulation factors XII (FXII) and XI (FXI) act as master regulators of several cascades including coagulation, fibrinolysis, complement activation, and inflammation . PK is an unusual plasma protease as it does not recruit its principal substrate high‐molecular‐weight kininogen (HK) upon activation but rather it circulates as a zymogen in a tightly bound but inactive PK‐HK complex , raising the question as to how this complex is effectively regulated.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of extracellular proteolysis is critical to blood hemostasis and innate immunity and proteases plasma prekallikrein (PK), and coagulation factors XII (FXII) and XI (FXI) act as master regulators of several cascades including coagulation, fibrinolysis, complement activation, and inflammation . PK is an unusual plasma protease as it does not recruit its principal substrate high‐molecular‐weight kininogen (HK) upon activation but rather it circulates as a zymogen in a tightly bound but inactive PK‐HK complex , raising the question as to how this complex is effectively regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Properdin can also bind, and subsequently stabilize, C3 convertase in the alternative pathway [22]. Studies have shown that the alternative pathway is initiated by not only properdin but also various proteases, including thrombin and kallikrein [24][25][26].…”
Section: Complement Systemmentioning
confidence: 99%
“…A further link between the contact system and host defense is activation of the alternative complement pathway by FXII that triggers activation of the C1 complex ( 31 ). In the alternative complement pathway, PK can replace factor D for the activation of C3 convertase ( 32 , 33 ). Simultaneous activation of the contact and complement system results in the generation of nascent molecules that have significant impact in various in inflammatory diseases including angioedema and cancer ( 34 ).…”
Section: The Pro-inflammatory Kallikrein–kinin System As a Link To Inmentioning
confidence: 99%